2021
DOI: 10.7554/elife.70068
|View full text |Cite
|
Sign up to set email alerts
|

Modality-specific tracking of attention and sensory statistics in the human electrophysiological spectral exponent

Abstract: A hallmark of electrophysiological brain activity is its 1/f-like spectrum - power decreases with increasing frequency. The steepness of this 'roll-off' is approximated by the spectral exponent, which in invasively recorded neural populations reflects the balance of excitatory to inhibitory neural activity (E:I balance). Here, we first establish that the spectral exponent of non-invasive electroencephalography (EEG) recordings is highly sensitive to general (i.e., anaesthesia-driven) changes in E:I balance. Bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
150
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(167 citation statements)
references
References 90 publications
14
150
3
Order By: Relevance
“…Importantly, failing to disentangle these factors contributing to the shape of the power spectrum could lead to erroneous conclusions regarding the mechanisms generating neural signals. Specifically, in our datasets, we observed a general steepening of 1/f activity from pre-to post-event, which would normally be interpreted as a shift towards inhibitory as opposed to excitatory activity (Colombo et al, 2019;Gao et al, 2017;Lendner et al, 2020;Miskovic et al, 2019;Waschke et al, 2021). However, our subsequent analyses indicate that it would be premature to conclude that auditory stimuli lead to increased inhibition.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 64%
See 3 more Smart Citations
“…Importantly, failing to disentangle these factors contributing to the shape of the power spectrum could lead to erroneous conclusions regarding the mechanisms generating neural signals. Specifically, in our datasets, we observed a general steepening of 1/f activity from pre-to post-event, which would normally be interpreted as a shift towards inhibitory as opposed to excitatory activity (Colombo et al, 2019;Gao et al, 2017;Lendner et al, 2020;Miskovic et al, 2019;Waschke et al, 2021). However, our subsequent analyses indicate that it would be premature to conclude that auditory stimuli lead to increased inhibition.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 64%
“…Notably, this possibility does not invalidate the popular account which posits that changes in the shape of 1/f activity reflect changes in the balance of excitatory and inhibitory neural inputs, regardless of the invasiveness of the recording (Gao et al, 2017;Waschke et al, 2021), given that activity elicited by an event (ERP) arguably -and trivially -also reflects a shift in the balance of excitation and inhibition in neural populations. Our findings, however, increase the explanatory power of this account by suggesting that 1/f-like scaling in the frequency domain of a signal might reflect a combination of stimulus-related and stimulus-unrelated (ongoing, background) activities that are both non-oscillatory in nature (i.e., they do not include ongoing alpha oscillations).…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work, however, has begun to provide compelling evidence in support of the importance of the aperiodic signal. Studies have shown aperiodic activity to be modulated by task-performance ( He et al, 2010 ), level of arousal ( Lendner et al, 2020 ), and drug-induced states ( Colombo et al, 2019 , Muthukumaraswamy and Liley, 2018 , Waschke et al, 2021 ). In addition, several studies have shown features of the aperiodic signal to be altered in neurological and psychiatric disease ( Molina et al, 2020 , Ostlund et al, 2021a , Robertson et al, 2019 , Wilkinson and Nelson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%